Unraveling the ties: exploring small family business partnership rebuilding and valuation - Vasconcelos, Guilherme Chim (2023)
This work project explores the grounds of reconstructing small family business partnerships, and how to value these firms when partnerships are broken. Exploring the grounds of entrepreneurship the research interviewed owners of family and non-family businesses of different sizes, in order to understand how they differ from each other, from theory and from the interviewed specialists. The findings reveal that most enterprises fail to repair their partnerships and are unpopular for hiring valuation experts, often valuing internally. These findings indicate that all enterprises need support in both topics. Research could impact the future of entrepreneurship with more findings.